IMF Staff papers : Volume 13 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1966)
From the Foreword to the first issue: 'Among the responsibilities of the International Monetary Fund, as set forth in the Articles of Agreement, is the obligation to fact as a center for the collection and exchange of information on monetary and financial problems,' and thereby to facilitate 'the preparation of studies designed to assist members in developing policies which further the purposes of the Fund.' The publications of the Fund are one way in which this responsibility is discharged. 'Through the publication of Staff Papers, the Fund is making available some of the work of members of its staff. The Fund believes that these papers will be found helpful by government officials, by professional economists, and by others concerned with monetary and financial problems. Much of what is now presented is quite provisional. On some international monetary problems, final and definitive views are scarcely to be expected in the near future, and several alternative, or even conflicting, approaches may profitably be explored. The views presented in these papers are not, therefore, to be interpreted as necessarily indicating the position of the Executive Board or of the officials of the Fund.'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet